Some issues on Murabahah practices in Iran and Malaysian Islamic banks. - Zandi Pour Joopari, GholamReza; Mohd Ariffin, Noraini; Shahabi, Alireza (Academic Journals, 2012)
The purpose of this paper was to analyze the nature of Murabahah contract in the fully grounded Islamic banking system that is, Iran and Malaysia. The approach taken was descriptive. Although, the main principle of Islamic financial institutions is prohibition of usury, it is surprising to see that Islamic financial institutions are still practicing usury in their transaction as evidenced in Iran. In the case of Malaysia however, BBA home financing is used by Islamic financial institutions and the profit rate is still dependent on the market interest rate due to arbitrage activities. There is no transparent framework for Murabahah contracts in Islamic banks. Indeed there is a need for the banking standard regulators to set a clear and disciplined framework for this type of banking contract. There are currently, Murabahah security (Sukuk) for finance, Murabahah security (Sukuk) for liquidity, companies Murabahah security (Sukuk) and mortgage Murabahah security (Sukuk) products in the Islamic niche of the financial market. A combination of Murabahah Security for Finance and Mortgage Murabahah Security has been the underlying Murabahah instrument. The study hopes to improve the overall competency and reliability of the Islamic banking system in the world. The finding of this study will be a basis for further research in Murabaha with respect to the regulatory environment and Shari’ah compliance.